Pengembangan Monopoli Berbantuan Augmented Reality Berbasis Pendekatan Culturally Responsive Teaching Materi Sistem Tata Surya - Hasanah, Imro’atul; Habiddin, Habiddin; Rudiyanto, Rudiyanto (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to develop MOANALISYA (Monopoli Augmented Nusantara Lingkup Sistem Tata Surya) learning media and to asses respondents' responses to its development. The developed media is expected to provide a pleasant learning experience for students so that the final results obtained are not only knowledge but also thinking, collaboration, communication, and kinesthetic skills. The study used a 4D development model (define, design, develop, disseminate) without conducting a disseminate stage. The data collection technique was tested on media experts, material experts, science teachers, and seventh-grade students of Sriwedari Middle School in Malang City in the 2024/2025 academic year with a sample of 10 students. The data analysis technique used percentage calculations to assess the validity and practicality of the Likert scale instrument. The results showed that the development of MOANALISYA received a positive response with a percentage of 85% from media experts and 84.38% from material experts indicating it is very valid and suitable for use in the learning process. In addition, the practicality test also entered the very interesting or very practical category after showing a positive response of 82.5% from teachers and 89.88% from students. Thus, it can be concluded that the MOANALISYA learning media is suitable for use in science learning on the solar system material.